Preventing postpartum hysterectomy in a district general hospital. (18th April 2012) - Carpenter, C; Thomas, K
Abstract : Postpartum Haemorrhage (PPH) is still one of the leading causes of obstetric mortality in the developed world. When pharmacological treatment has failed, there are various surgical treatment options that should be considered prior to hysterectomy. These include; ▶ Uterine/Internal Iliac Artery Ligation ▶ Uterine artery embolisation ▶ B Lynch Suture ▶ Rusche Catheter/Baloon tamponade We reviewed cases of postpartum hysterectomy over a 10 year period in a DGH with 3, 200 deliveries a year to see if they could have been prevented, and what lessons could be learned for future cases. There were 9 cases of Postpartum Hysterectomy in the study period. Reasons for hysterectomy were as follows; ▶ 4 Placenta Accreta ▶ 2 Uterine atony ▶ 1 Bleeding from lower segment / extension / 'unsavable lower segment' ▶ 1 Sepsis following CS (done 6 days post caesarean) ▶ 1 posterior uterine wall rupture In the 10 year period uterine artery embolisation and internal Iliac artey ligation were never used. B lynch suture was used 5 times and was unsuccessful in one case of atony that had a hysterectomy. A Rusche catheter was not used in the 2 cases of uterine atony, where it may have prevented hysterectomy highlighting the importance of including this in obstetric skills drills. No cases of placenta accreta were diagnosed pre delivery when embolisation could be useful. This study highlighted the importance of teaching other methods and highlighting them in obstetric skills drills involving trainees. It also highlighted a deficiency in our service by not providing embolisation.